THE EFFECT OF LEG EXTENTION TRAINING ON THE LEG MUSCLE STRENGTH OF FOOTBALL PLAYERS AT SMA NEGERI 3 BANJARBARU - Rachman, Aryadi; Ridha, Sahbana; Saputra, Deny Bagus; Erfandy, Wahyu (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2024)
Leg muscle strength is an essential component in supporting the performance of soccer athletes, particularly in terms of speed and kicking power. Leg extension exercises are a form of resistance training focused on strengthening the quadriceps (front thigh muscles) by lifting weights with the legs while seated on a leg extension machine. The aim of this study is: to determine whether there is the effect of exercise on the leg extension leg muscle strength of soccer player SMAN 3 Banjarbaru. This research uses quantitative methods of pre-experimental. The study design used pretest and posttest in One Group. The population in this study is a soccer player of SMA 3 Banjarbaru of 20 people, then a sample total sampling technique or sample is saturated. The survey results revealed that leg extension exercise influences leg muscle strength in soccer players SMAN 3 Banjarbaru in accordance with the criteria of testing the value of Sig. (2-tailed) 0.000 <0.05. Leg extension exercise resulted in an increase in leg muscle strength in soccer players SMAN 3 Banjarbaru amounted to 15 440.